Pengaruh Pelabuhan Perikanan Pantai Tegalsari terhadap Kesejahteraan Pekerja - Arief Diantoro; Mussadun Mussadun (Jurnal Wilayah dan Lingkungan, 2015)
The existence of Pelabuhan Perikanan Pantai Tegalsari (PPP Tegalsari) or Tegalsari Fishing Harbor (TFH) is closely linked to the local livelihood where the job opportunities available to the local residents in pursuit of better living standards. However, there are economic disparities between the workers and business owners so that income inequality remains a critical issue here. This study aims to explore the activities in TFH and their influences on the workers' welfare. This study applies both quantitative and qualitative approaches. The former is applied for identifying the leading sectors and their impacts on the worker's welfare, and the latter is to explaining their activities comprehensively. The findings demonstrate that there are four main activities in TFH: services, trade, fishing enterprises, and supporting activities. The service activities are the leading sector with a score of 16. Meanwhile, the highest influencing activity which contributes to the workers' welfare is service activities with a score of 435. The study concludes that the activities in the TFH positively correlate to their income level which in turn contributes to their welfare improvement. Therefore, the government is recommended to providing greater service supports and the associated activities in order to create more equitable opportunities for all sectors. As for the business owners and private sectors, they are encouraged to pay more attention to their workers’ welfare from which the local economy could be accelerated.